Pendampingan Perbaikan Kemasan dan Uji Kandungan Nutrisi Jus Kweni (Mangifera odorata) UMKM Indira House, Kabupaten Bogor - Sherly Eka Maulidiya; Salma Firyal Khairunnisa; Theresia Aprilia Sianipar; Yulia Sari; Muhammad Syukur; Muhammad Isbayu (Institut Pertanian Bogor, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy. MSMEs often face challenges in business development, especially in improving product quality and their competitiveness in the market. This mentoring activity aims to assist Indira House MSMEs in Bogor Regency in improving the packaging and testing the nutritional content of kweni products to improve product quality. The nutritional tests will be listed on the new packaging label. Assistance for improving packaging quality also includes improvements to the visual aspects, color, type of letters, labeling and information, and uniqueness and functionality of the packaging. Overall, this assistance was successful in several important aspects, including an increase in consumer assessment of various aspects of packaging, from visuals, labeling, and color to functionality. The packaging improvements were well received by consumers and increased the product appeal. Sales are more stable, despite monthly fluctuations, and sales trends show that products with new packaging can attract consumer interest. Consumer trust and loyalty, clear nutritional information, and functional packaging build consumer confidence, which is important for repeat purchases and long-term loyalty. Competitiveness in the market, with more attractive packaging and clearer information, Indira House kweni juice is able to compete better in the market. This assistance provides a strong basis for Indira House MSMEs to continue developing their products and increase their competitiveness in the market. With the right marketing strategy and continuous improvement in product quality, sales and consumer satisfaction are expected to continue to increase in the future.